Blood Glucose Management Protection Motivation Trajectory and Its Associated Factors in Pregnant Women with Gestational Diabetes Mellitus: A Longitudinal Study - Gao Y; Liu J; Zhu Q; Zhang Z; Dai Q; Guo Y; Zhang W; Jia M (Patient Preference and Adherence)
Yi Gao,1 Jun Liu,2 Qingxian Zhu,2 Zhiyi Zhang,2 Qi Dai,2 Yifan Guo,2 Wei Zhang,2 Minjie Jia1 1Wuxi Medical College, Jiangnan University, Wuxi, Jiangsu, People’s Republic of China; 2The Affiliated Maternity and Child Health Hospital of Jiangnan University, Wuxi, Jiangsu, People’s Republic of ChinaCorrespondence: Jun Liu, The Affiliated Maternity and Child Health Hospital of Jiangnan University, No. 48, Samuel Lane, Liangxi District, Wuxi, Jiangsu, People’s Republic of China, Tel +86 133 8287 0903, Email 1453210303@qq.comPurpose: To (1) explore the trajectories of blood glucose management protection motivation in pregnant women with gestational diabetes mellitus, based on a growth mixture model, and (2) identify factors associated with these trajectories.Patients and Methods: This longitudinal study, conducted between December 2023 and June 2024 at a tertiary hospital in China, involved 313 pregnant women diagnosed with gestational diabetes mellitus who were not using medication to control their blood glucose levels. Participants were assessed at three time points: 24– 28 gestational weeks, 29– 35 gestational weeks, and 36– 40 gestational weeks. The data collected included general demographic information and the level of blood glucose management protection motivation. A growth mixture model was employed to examine the trajectory of blood glucose management protection motivation, and binary logistic regression analysis was performed to identify predictors of the trajectory. This study was reported following the Reporting Observational Longitudinal Research statement.Results: The study identified two distinct trajectories of blood glucose management protection motivation: a low-motivation group (slowly increasing then rapidly declining; 124, 39.62%) and a high-motivation group (rapidly then increasing slowly declining; 189, 60.38%). The independent predictors of these trajectory categories included age, per capita monthly household income, and pregnancy complications.Conclusion: Significant heterogeneity existed in the developmental trajectories of blood glucose management protection motivation among pregnant women with gestational diabetes mellitus. Future research should prioritize developing targeted interventions that consider not only different developmental trajectories but also factors such as age, per capita monthly household income, and pregnancy complications. These strategies may foster blood glucose management protection motivation among pregnant women with gestational diabetes mellitus, addressing their specific needs and enhancing the effectiveness of care.Keywords: blood glucose management, gestational diabetes mellitus, longitudinal study, protection motivation, trajectories